Development and Initial Psychometric Assessment of the Reasons for Pretending Orgasm Inventory. (1st January 2015) - McCoy, Mark G.; Welling, Lisa L. M.; Shackelford, Todd K.
Research suggests that women pretend orgasm with their partner as a mate retention strategy, but the cognitive reasons behind this deception are not well known. To explore women's cognitive reasons for pretending orgasm, we first assembled a list of the reasons women report for pretending orgasm. We refined this list using independent data collected on performance frequencies for each item, followed by a principal components analysis, to generate the Reasons for Pretending Orgasm Inventory (RPOI). We found three components encompassing the cognitive reasons women pretend orgasm: Improve Partner's Experience (i.e., increasing the quality of the sexual experience for the partner), Deception and Manipulation (i.e., deceiving the partner or manipulating his perceptions for other gains), and Hiding Sexual Disinterest (i.e., sparing the partner's feelings about the woman's lack of sexual excitement). Discussion highlights limitations of this research and the RPOI, but suggests that the RPOI is useful as a structured means for assessing women's reasons for pretending orgasm.